Digital Divide, Human Capital, and Employment Opportunities for Married Women - Nur Haminati; Arif Zulkarnain; M Hamid; Rezi Setiawan (SAFE-Network, 2026)
This study discusses the influence of the use of digital technology and human capital on the employment opportunities of married women in Riau Province. The scope of the study was focused on women of working age and married status by considering socioeconomic factors that may affect their participation in the labor market. The purpose of this study is to analyze whether the use of digital technology can increase the chances of married women to work, as well as identify other factors that play a role in women's decision to enter the job market. This study uses a quantitative approach with the logistic regression method. The data used was sourced from the National Labor Force Survey in August 2022 with 6347 observations of women's productive age and married status. The dependent variable in this study is the working status of married women, while the main independent variable is the use of digital technology and the purpose of using the internet for productive activities. Control variables included education, age, training, and area of residence. The results of the study show that the use of digital technology has a positive effect on the chances of married women to work. Although the use of digital devices increases employment opportunities, there is a digital divide in married women that the digital access obtained in general has not been used for the purpose of activities of economic value by married women. In addition, education and training also play an important role in increasing women's employment opportunities. The main conclusion of this study is that digital technology can be an important instrument in expanding women's access to job information, business opportunities, and productive economic activities if there is no digital divide caused by low digital literacy to the lack of understanding of married women in utilizing this access. Thus, these benefits need to be supported by increasing digital literacy, online skills improvement programs, digital-based entrepreneurship socialization and inclusive employment policies.